PKM Pelatihan Pemanfaatan Bahan Bekas Sebagai Media Pembelajaran IPA bagi Kelompok Guru IPA - Duda, Hilarius Jago; Awang, Imanuel Sairo; Andri, Andri (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Based on observations at SMP Nusantara Indah Sintang and SMP Panca Setya 2 Sintang as a schoolspartner, it is seen that the condition of the laboratory is inadequate wherethe available of the tools and materials are less. Science Teachers did not innovate and create creations to overcome the problem. In addition, practicum activities are rarely done, including in utilizing the surrounding environment. Science Teachers tend to do learning process with theory. Therefore, the joint proponent cooperates to overcome the problem through the program of Pengabdian Kepada Masyarakat (PKM). This PKM program is aims to improve teachers' skills in designing and developing learning media with unused materials. The method used in the achievement of the goal is the implementation of inservice in the form of training and mentoring. The training was carried out is the training of techniques to design learning media with used materials. The results of the training is there are six media developed i.e linear motion, simple machine, digestive system, additive substances, structure and function of plant tissue, and circulatory system.